2008
DOI: 10.1088/0004-6256/135/4/1318
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Fragmenting Dust Particles From Near-Simultaneous Optical and Near-Infrared Photometry and Polarimetry of Comet 73p/Schwassmann-Wachmann 3

Abstract: We report imaging polarimetry of segments B and C of the Jupiter-family comet 73P/Schwassmann-Wachmann 3 in the I and H bandpasses at solar phase angles of approximately 35• and 85• . The level of polarization was typical for active comets, but larger than expected for a Jupiter-family comet. The polarimetric color was slightly red (δP /δλ = +1.2 ± 0.4) at a phase angle of ∼35• and either neutral or slightly blue at a phase angle of ∼85 • . Observations during the closest approach from 2006 May 11-13 achieved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
4
20
1
Order By: Relevance
“…In the inner coma (less than 400 km from the optocenter and out of the region blurred by seeing (130 km in average), all the profiles present smaller slopes than -0.7 most likely because of the presence of multi-jets mainly on April 28 and May 3, with breaking of the particles and dynamical effects. These later interpretations were also suggested by Jones et al (2008), who observed also a flattened slope in the inner coma. The three sunward profiles become steeper for optocentric distances larger than 3000 km with a very important increase of the slope on May 3 suggesting that particles leave the coma pushed back by the solar radiation pressure and can be found tailward.…”
Section: Fragment Csupporting
confidence: 67%
See 3 more Smart Citations
“…In the inner coma (less than 400 km from the optocenter and out of the region blurred by seeing (130 km in average), all the profiles present smaller slopes than -0.7 most likely because of the presence of multi-jets mainly on April 28 and May 3, with breaking of the particles and dynamical effects. These later interpretations were also suggested by Jones et al (2008), who observed also a flattened slope in the inner coma. The three sunward profiles become steeper for optocentric distances larger than 3000 km with a very important increase of the slope on May 3 suggesting that particles leave the coma pushed back by the solar radiation pressure and can be found tailward.…”
Section: Fragment Csupporting
confidence: 67%
“…comet Hale-Bopp (Hadamcik et al, 2003b;Kelley et al, 2005). The infrared data in the I band obtained by Kiselev et al (2008) are always below the red ones on the whole phase angle ranges 38°-73° for both fragments, and are very low as compared to values obtained by Jones et al (2008) These values seem to contradict the other results (Fig. 5).…”
Section: Comparison Between Polarimetric Observations Of Sw3 and Thoscontrasting
confidence: 64%
See 2 more Smart Citations
“…Assuming this dust composition, particles of radius 10 μm are, for example, bluer than particles of radius 1.5 μm, at the phase angle of our image. Moreover, grain aggregates breakup and fragmentation were found to reproduce well the observed brightness radial profiles perpendicular to the Sun-comet axis of component B on May 11−13 by Jones et al (2008), who analyzed optical and near-IR data in the H, I filters. This perpendicular direction gives a cross-cut of the arc feature we detected in the same date.…”
Section: Dust Colorsmentioning
confidence: 56%